Effect of demographic variables on public attitude towards genetically modified insulin - Amin, Latifah; Zainol, Zinatul Ashiqin; Md Jahi, Jamaluddin; Md Nor, Abd Rahim; Osman, Mohamad; Mahadi, Nor Muhammad (Academic Journals, 2011)
Earlier studies on public attitude and risk perception have concluded that the public’s attitudes towards biotechnology was primarily driven by several factors such as familiarity, perceived benefits, perceived risks, risk acceptance, moral concerns and encouragement. Demographic characteristics have been known to affect attitudes towards science. The purpose of this paper is to compare the attitude of the Malaysian public towards genetically modified (GM) insulin across several background variables such as religion, race, education level and age. A survey was carried out on 1017 respondents stratified according to various stakeholder groups in the Klang Valley region. Analyses of Variance (ANOVAs) showed significant differences in the mean scores for familiarity of GM insulin across religions, races and ages but not across education levels and gender. Both perceived benefits and perceived risks were found to differ across races, education levels and gender but not across religions and ages. On the other hand, moral concern was found to differ in all four background variables except gender while risk acceptance differed across races and gender and encouragement only differed across education levels. In conclusion, background variables do have a significant effect on some of the dimensions of Malaysians’ attitudes towards modern biotechnology. The research findings will be useful for understanding the effect of background variables on public attitudes towards the application of gene technology in medicine. More in-depth empirical studies should be carried out to understand the underlying causes behind the differences.